The church in the square: negotiations of religion and revolution at an evangelical church in Cairo, Egypt - Dowell, Anna (AUC Knowledge Fountain, 2012)
In the wake of the Egyptian January 25, 2011 popular uprisings that deposed Hosni Mubarak from the presidency, youth and leaders from Kanisset Kasr el Dobara (KDEC) in Tahrir Square embarked on new and unpredictable political projects and activisms. This ethnographic study is an engagement with these new revolutionary negotiations on the part of the largest Protestant congregation in the Middle East. Using participant observation, focus groups, and interviews this research seeks to elucidate the ways that youth and leaders utilized institutionalized discourse, religious imagery, and relational networks in order to carve out a place in the Egyptian public sphere regarding public religion, national belonging, and the ideal citizen. Broadly this research seeks to understand how Evangelical Egyptians at KDEC navigated their colonial heritage and transnational character even as their leadership sought to ground the congregation in the Egyptian nation-state and in the emerging post-revolutionary political scene. I argue that these negotiations were built upon powerful paradoxes concerning liberal politics, secularism, and private versus public religion, which often implicated Evangelicals in the same questions being raised more broadly in the Egyptian political sphere concerning Islamist politics and religious minorities. These negotiations also serve as a significant departure from the political posture and intervention of the much larger Coptic Orthodox establishment in Egypt. This project contributes to literature on the formation of religious subjectivity and political imaginaries, the nexus between Protestantism and modernity, as well as the role and future of public religions, especially as these topics are being pursued in the anthropology of Christianity.